The Effect of Work Motivation and Work Stress on Employee Performance at Perum Damri Lampung - Achmad Riwanda; Rina Loliyana; Helmita Helmita (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study examines the influence of work motivation and job stress on the performance of AKAP (Intercity Interprovincial Transport) bus drivers at Perum DAMRI Lampung Branch. Using a quantitative approach with multiple linear regression analysis, the research involved a population of 112 drivers, with a purposive sample of 53 respondents. The findings indicate that work motivation has a positive and significant effect on driver performance ( p = 0.613; Sig. = 0.000), suggesting that higher motivation enhances performance. Conversely, job stress has a negative and significant impact (p = -0.551; Sig. = 0.000), meaning increased stress decreases performance. Simultaneously, work motivation and job stress significantly influence driver performance (F = 77.167; Sig. = 0.000). The study concludes that improving work motivation and managing job stress effectively are key strategies for enhancing the performance of AKAP bus drivers. However, the research is limited to drivers at the Perum DAMRI Lampung Branch, and the results may not be generalizable to other contexts. The study contributes empirical evidence emphasizing that motivation and stress management are critical determinants of driver performance within transportation organizations.